Predictive Factors of Cerebral Aneurysm Rerupture After Clipping - Chang, Yu-Jun; Liu, Chi-Kuang; Cheng, Chun-Yuan; Shih, Yu-Cheng; Wang, Shih-Chun; Lin, Chung-Chih; Lin, Chih-Ming (Frontiers in Neurology, 2022)
Background We aimed to estimate the risk of rerupture after first-time aneurysmal clipping surgery, explore the possible related factors, and assess long-term physical functionality. We hypothesized that the modified Rankin scale (mRS) could serve as an effective substitute for Hunter and Hess scale. Methods This retrospective study included 171 patients with cerebral aneurysmal rupture who had completed aneurysmal clipping treatment and collected their demographic data and medical records. The outcome assessments include neuroimaging records, Hunter and Hess scale, and the mRS scale during hospitalization and follow-up after discharge. The mean length of follow-up was 4.28 years. Results After aneurysmal clipping treatment, 83 patients (48.5%) had subsequently ruptured aneurysms. The scores of the reruptured group on the Hunt and Hess scale and mRS were significantly higher than those of the non-reruptured group. Multiple Cox proportional-hazards regression also showed that postoperative mRS >2, smoking, and two or more aneurysms were potentially important risk factors leading to aneurysm rupture again [the corresponding hazard ratios (HRs) were 5.209, 2.109, and 2.775, respectively] in patients. In addition, the location of an aneurysm on the anterior cerebral artery (ACA) or the posterior communicating (Pcom) artery had a higher risk of rerupture (the corresponding HRs were 1.996 and 2.934, respectively). Conclusions Nearly half of the collected participants experienced the rerupture episode, who had undergone the second-time clipping surgery. Smoking and multiple aneurysms are potential risk factors for aneurysmal rerupture. Most aneurysms are located along the ICA, but aneurysms located at the ACA or Pcom site are most likely to rerupture. As compared with the Hunter and Hess scale, the mRS scale does not have inferior predicting power in following patients' long-term functionalities.